Changes in the management of liver trauma leading to reduced mortality: 15‐year experience in a major trauma centre. Issue 11 (2nd August 2015) - Suen, Kary; Skandarajah, Anita R.; Knowles, Brett; Judson, Rodney; Thomson, Benjamin N.
Abstract: Background: Worldwide, the evolution of management of liver injury has resulted in improved outcomes. The aim of this study was to examine the trend in the management and outcomes of patients with liver injury. Primary outcomes were defined as mortality and hospital length of stay. The secondary aim was to identify independent predictors of mortality. Methods: This study utilized hospital trauma registry data of all trauma patients with liver injuries admitted from 1999 to 2013. Patients in this 15‐year period were divided into three periods of 5 years each and compared in terms of demographics, management and outcomes. Results: A total of 725 patients with hepatic trauma were included. Patient demographics were similar, except for an increase in patient transfers from rural locations. Non‐operative management increased significantly. There was a significant increase in the use of damage control surgery with perihepatic packing in high‐grade liver injuries managed operatively. Hepatic angioembolization commenced midway through the study period. The overall mortality decreased by approximately threefold ( P < 0.001) and mortality within 24 h of arrival to hospital by approximately fivefold ( P < 0.001). Controlling for independent predictive factors of mortality, the mortality within 24 h reduced from 18.8% in period 1 to 3.6% in period 3 ( P = 0.001). Conclusions: At this institution, an integrated trauma service has led to an evolution in the management of hepatic trauma, favouring non‐operative management, damage control surgery and the use of hepatic angioembolization. We experienced a significantly improved mortality within 24 h of arrival to hospital in patients with liver trauma.